Gen Z And E-Bikes: The Impact Of Environmental Awareness - Ni Nyoman Dwi Adnyani; Nilna Muna (UNIVED Press, 2025)
Growing environmental awareness is driving interest in green transportation such as electric bicycles. Generation Z, with their environmental concerns and technological prowess, is a key market, yet research on their purchasing behavior is limited. This study aims to analyze the influence of Environmental Awareness and Green Perceived Value on Green Purchase Intention in the purchase of electric bicycles among Generation Z in Bali, with Green Attitude as a mediating variable. This research uses a quantitative approach with the Partial Least Squares (PLS) analysis method. ========= Data were collected through a structured questionnaire from 128 respondents selected by purposive sampling method. The results showed that Environmental Awarenes and Green Perceived Value have a significant effect on Green Purchase Intention, with Green Attitude as a mediating variable. These findings contribute to the understanding of green consumer behavior, especially among Generation Z.